Somatic Symptoms: Association Among Affective State, Subjective Body Perception, and Spiritual Belief in Japan and Indonesia - Maulina, Venie Viktoria Rondang; Yogo, Masao; Ohira, Hideki (Frontiers in Psychology, 2022)
This study aimed to examine differences in the following somatic symptoms: affective state (i.e., health concerns, anxiety, and positive and negative affect), somatosensory amplification, spirituality in Japan and Indonesia, and associations among all variables from each culture. Previous studies and a potential bio-psycho-spiritual model has identified the association of each variable in the development of somatic symptoms. Moreover, they demonstrated that individuals who describe themselves as more religious and spiritual report better physical and mental health. A total of 469 and 437 university students from Japan and Indonesia, respectively, completed the questionnaires for assessing somatic symptoms, health concerns, trait anxiety, positive and negative affect, somatosensory amplification, and spiritual belief. This study found significant differences in health concerns, positive and negative affect, state anxiety, and spiritual belief. Moreover, the difference in somatosensory amplification was negligible. There is a shared association in both cultures among somatic symptoms, affective state, subjective body perception, and spirituality. Health concerns and trait anxiety moderated somatosensory amplification in the development of somatic symptoms. However, the role of spirituality belief in somatic symptoms was observed in the Japanese and Indonesian cultures in relation to positive affect.